A new level of gene regulation: establishing a genome-wide role for antisense transcription - Murray, S; Struan Charles Murray (2013)
Transcription lies at the centre of gene expression. In eukaryotes, transcription occurs not only at genes but also across the non-coding portion of the genome, an apparently pervasive process that gives rise to a wide array of different transcripts. In recent years, it has emerged that genes themselves are frequently subject to non-coding transcription of their antisense strand. This antisense transcription is evident in eukaryotes from yeast to mammals; however its general genome-wide role, if indeed it has one, remains elusive. Here, the nature of antisense transcription in the budding yeast Saccharomyces cerevisiae is explored on a genome-wide scale. Antisense transcription is ubiquitous and often abundant, and appears to be driven by a promoter architecture at the 3’ end of genes, one which shows evidence of regulation, and which mirrors that found at the 5’ end. Furthermore, antisense transcription shows evidence of changing gene behaviour. It is associated with a drastically altered chromatin environment at the 5’ promoter and across the gene body; however it is not associated with a change in the level of gene transcription itself. Rather, these chromatin changes appear to enforce a change in the mode of gene transcription, promoting rapid bursts of transcription re-initiation that result in noisier gene expression – a hitherto unknown role of antisense transcription. It is proposed that antisense transcription represents a fundamental layer of gene regulation, and that it should be considered a canonical feature of eukaryotic genes.